Purification and cryo-EM structure determination of VCP/p97 dodecamers from mammalian and bacterial cells - Guimei Yu; Yunpeng Bai; Zhong-Yin Zhang (STAR Protocols, 2022)
Summary: Valosin-containing protein (VCP, also known as p97/Cdc48) comprises six identical 97 kDa VCP protomers and functions as a master regulator of cellular homeostasis. VCP dodecamer in an apo nucleotide status was recently reported, providing a new framework for studying VCP’s diverse biological functions. Here, we present a detailed protocol for purifying and cryo-EM structurally characterizing VCP dodecamers from both bacterial and mammalian cells. This protocol can also be adapted to yeast Cdc48.For complete details on the use and execution of this protocol, please refer to Yu et al. (2021).